Gambaran Pelaksanaan Pendekatan Cooperative Learning Pada Pembelajaran Sosiologi Kesetaraan Paket C - Syilvi Amar; Setiawati Setiawati (PAKAR Pendidikan, 2019)
This research was motivated by the good implementation of Sociology learning. This was presumably because of cooperative learning approaches used in learning. This study aimed to: (1) describe the implementation of the initial activities in Sociology learning through a cooperative learning approach, (2) describe the implementation of core activities in Sociology learning through cooperative learning approaches, and (3) describe the implementation of evaluations in Sociology learning through cooperative learning approaches. This research includes descriptive quantitative research. The populations in this study were 30 people. The sampling technique was simple random sampling with the sample of 20 people. The technique and data collection were questionnaires with statement questionnaires. Data analysis techniques used percentages. The results show that: (1) the implementation of the initial activities in Sociology learning through cooperative learning approach is good, (2) the implementation of core activities in Sociology learning through cooperative learning approach is good, and (3) the implementation of initial activities in Sociology learning through cooperative approach learning is good. The suggestion of this study is to tutor Package C Sociology subject in order to further improve the implementation of sociology learning with cooperative learning approaches so as to further enhance the learning spirit and learning outcomes of the citizens.